Navigating the Struggles of Beedi Workers Using the Garrett Ranking Approach: A Case Study of Jangipur Subdivision, Murshidabad - Doha, Kismode; Ahmad, Syed Naushad (CV. Literasi Indonesia, 2025)
Beedi making is an integral part of the country’s unorganised sector, wherein labor is predominantly sourced from impoverished classes of society; Jangipur subdivision of Murshidabad is no exception. To rank the challenges faced by beedi workers comprehensively and objectively, this research applies the Garrett Ranking Technique. The analysis highlights that concern with health, inadequate income, and long working hours are some of the most significant stressors experienced by workers. Sickness and diseases are the results of long exposure to tobacco and unfavorable working conditions, low wages, and long hours of work, which compound economic difficulties. However, job insecurity and the lack of access to welfare measures for the population remain critical issues due to the informal nature of work. Furthermore, social prejudice for manual jobs is connected with the social status of the workers, but it appears to be diminishing due to higher literacy levels. Accordingly, the called for policy aids encompassing occupational health and other socio-economic domains of the beedi workers’ lives corroborate this study’s call to consider developing policy initiatives to support the physical, financial, and socio-security status of beedi workers, and in the process, facilitating social upliftment for them and serve as a guide for designing intervention strategies in this beleaguered segment of the workforce.